Distribuição espacial do bicho-furão, Gymnandrosoma aurantiana (Lima, 1927) (Lepidoptera: Tortricidae), em citros utilizando geoestatística - Carvalho, João Henrique Silva [UNESP]; Barbosa, José Carlos [UNESP]; Yamamoto, Pedro Takao; Bicalho, Izabela Bezzon [UNESP] (FapUNIFESP (SciELO), 2015)
The citrus fruit borer, Gymnandrosoma aurantiana (Lima, 1927), is one of the most important pests of citrus in Brazil, mainly because the larvae render the fruit useless for both fresh consumption and industrial processing. It was aimed to study the spatial distribution of fruits attacked by G. aurantiana using geostatistics. Thus, an experiment was carried out in a ‘Valencia’ sweet orange orchard, located in the municipality of Taquaritinga, state of São Paulo, Brazil. The experimental area was divided into 88 sampling units, consisting of 30 plants (three rows x ten plants), and then it was recorded the number of fruits attacked by G. aurantiana in 2007 and 2008. The spatial distribution of attacked fruits was aggregated for both sampling periods, and the variance was greater than the mean for all samplings. The data showed proper adjustment to the spherical model, and the range of spatial dependence (a) varied from 40.66 to 135.40 m. Kriging was used in order to estimate the attacked fruits at not sampled sites, and it was shown that the damage was mainly done at the sampling units that were near the border of the experimental field.
Spatial distribution of citrus fruit borer, Gymnandrosoma aurantiana (Lima, 1927) (Lepidoptera: Tortricidae), on citrus by using geostatistics
Keywords: Clumped pattern; Kriging; Moth; Semivariogram